THE STAGES OF POSTURE FORMATION AND VARIOUS FACTORS LEADING TO A CHANGE IN POSTURE (LITERATURE REVIEW) - Sayyora M. Axmedova; Dilrukh I. Khodjaeva (Central Asian Journal of Medicine, 2023)
Posture has attracted the attention of doctors and scientists since time immemorial. Early studies were exclusively practical in nature and were associated with pathological conditions of the spine. Hippocrates (460-377 BC) wrote several works on spinal curvature, in which he proposed methods for correcting body posture defects in the form of breathing exercises [9]. An equally popular ancient physician Galen from Pergamon described the treatment of scoliosis with the help of breathing exercises, singing and special chest bandaging [3]. It was he who first introduced the concepts of lordosis, kyphosis and scoliosis.